2022
DOI: 10.6024/jmbai.2022.64.1.2292-10
|View full text |Cite
|
Sign up to set email alerts
|

Organic carbon storage in sediments of seagrass habitats in the lagoons of Lakshadweep Archipelago, west coast of India

Abstract: Vegetated habitats like mangroves, seagrasses and saltmarshes capture and store carbon and act as carbon sinks. The carbon captured and stored in these habitats, especially in the belowground sediments, is called blue carbon. We report the blue carbon storage potential of seagrass habitats from the lagoons of Agathi, Bangaram, Kavaratti, Kalpitti, Thinnakara and Parli Islands of the U.T. of Lakshadweep. Sediment core samples were collected in triplicate from 30 cm deep from six stations located in the lagoons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Recent studies on the capture and burial of carbon (Kaladharan et al, 2022) in six islands of Lakshadweep Atolls indicated poor rates when compared with that of the Indian Archipelago. This is considered mainly due to degraded seagrass patches.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies on the capture and burial of carbon (Kaladharan et al, 2022) in six islands of Lakshadweep Atolls indicated poor rates when compared with that of the Indian Archipelago. This is considered mainly due to degraded seagrass patches.…”
Section: Discussionmentioning
confidence: 98%
“…It's found that the visual census method was effectively employed for the reef fish diversity documentation from the various parts of the country. From Lakshadweep Pillai 2002, 2005), the Andaman and Nicobar Islands (Madhu and Madhu 2007;Rajaram and Nedumaran, 2009) and from islands off the central western coast states of Goa and Karnataka (Sluka and Lazarus 2004, 2006Zacharia et al 2008;Thomas et al 2011). Another version of UVC, the rapid surveys have an immense role in the ichthyofaunal diversity study especially in an ecosystem like rocky reefs which deserve a more conservative approach for biodiversity assessment (Rajan et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The species is reported from Karnataka coast (Zacharia et al 2008). The species was previously listed out in the author's own study (Baiju et al 2016(Baiju et al , 2019.…”
Section: Remarksmentioning
confidence: 99%
See 1 more Smart Citation